Age-dependent effects of tobacco smoke and nicotine on cognition and the brain: A systematic review of the human and animal literature comparing adolescents and adults - Karis Colyer‐Patel; Lauren Kuhns; Alix Weidema; Heidi M. B. Lesscher; Janna Cousijn (2023)
Cigarette smoking is often initiated during adolescence and an earlier age of onset is associated with worse health outcomes later in life. Paradoxically, the transition towards adulthood also marks the potential for recovery, as the majority of adolescents are able to quit smoking when adulthood emerges. This systematic review aimed to evaluate the evidence from both human and animal studies for the differential impact of adolescent versus adult repeated and long-term tobacco and nicotine exposure on cognitive and brain outcomes. The limited human studies and more extensive yet heterogeneous animal studies, provide preliminary evidence of heightened fear learning, anxiety-related behaviour, reward processing, nicotinic acetylcholinergic receptors expression, dopamine expression and serotonin functioning after adolescent compared to adult exposure. Effects of nicotine or tobacco use on impulsivity were comparable across age groups. These findings provide novel insights into the mechanisms underlying adolescents' vulnerability to tobacco and nicotine. Future research is needed to translate animal to human findings, with a focus on directly linking a broader spectrum of brain and behavioural outcomes.